Potential effect of potting resin on the performance of hollow fibre membrane modules in a CO2/CH4 gas separation system - Ismail, A. F.; Kumari, S. N. (2004)
This study investigates the effects of epoxy and polyurethane resins when utilised as a potting resin in a hollow fibre membrane module used for CO2/CH4 separation. Due to swelling and shrinkage of the tubesheet, the permeation flowrates observed have shown significant fluctuations, thus, affecting the overall purity obtained by a membrane module. This clearly shows that not only the quality and variation of the hollow fibre membranes affect the results obtained by a hollow fibre membrane module, but also the selection of potting resins. Four samples comprising of 2 epoxy samples and 2 polyurethane samples were used to pot 50 strands of polysulphone hollow fibre membranes from the same batch of spinning. Utilising different feed concentrations of CO2/CH4 gases and operating pressures, permeation flowrates for the modules potted with the four samples were observed using a hollow fibre membrane gas separation testing apparatus. This study found that as Tg of the samples increased, plasticisation levels of samples lowered. In addition, this study also found that an increase in CO2 concentration corresponds with the increase in the degree of plasticisation for all samples, which causes a decrease in Tg, which directly causes a drop in its modulus of elasticity. Therefore, suggesting that potting resins with higher Tg are more compatible for CO2/CH4 gas separation systems.